PENGENALAN KOSAKATA BAHASA INGGRIS MENGGUNAKAN MEDIA VIDEO KEPADA ANAK-ANAK KELAS 2 DI SEKOLAH DASAR BUDI MULIA: ENGLISH VOCABULARY INTRODUCTION USING VIDEO MEDIA TO GRADE 2 CHILDREN AT BUDI MULIA ELEMENTARY SCHOOL - Zaitun Qamariah; Hesty Widiastuty; Alvin Maulana; Muhammad Rafi Zidan; Ahmad Julianto; Ahmad Basahil (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Mastery of English vocabulary is very important in preparing the younger generation to face future challenges. This research investigates the efficacy of using video media, especially animation, as an innovative learning tool for teaching English vocabulary to children. Previous research has shown that video media, including animation, significantly helps children understand and retain English vocabulary. Considering the optimal learning conditions for elementary school students, which are characterized by fun games and experiences, the use of video media is expected to create an interesting learning environment and increase student interest. This research uses a qualitative approach that combines participant observation and documentation. These findings underline the positive impact of video media, especially animation, on English vocabulary acquisition. Challenges such as limited time and teachers' unfamiliarity with using video media are also known. This research determines the influence of teacher motivation factors, parental support, and student activity in the learning process. Furthermore, this research not only highlights the role of video media in teaching English vocabulary but also explores strategies to improve children's learning outcomes and overcome learning barriers.